Pelatihan Membuat Website Sederhana Dengan Canva Untuk Calon Guru PAUD - Astini, Baik Nilawati; Gunawan, Gunawan; Rachmayani, Ika; Nurhasanah, Nurhasanah; Imran, Imran; Johdi, Haerul (Indonesian Journal of Education and Community Services, 2024)
This activity aimed to enhance their digital literacy and skills in creating innovative learning media. The training focused on using the user-friendly Canva platform for website design and development. A community service activity in the form of training on creating simple websites using Canva was conducted for 48 prospective early childhood education teachers at FKIP Unram. The evaluation was carried out by assessing the websites produced by participants using a Likert scale on five aspects: Content and Substance, Design and Aesthetics, Functionality, Technical Aspects, and Work Process. The evaluation results showed that participants successfully mastered the website development process (average 3.89), functionality (average 3.79), and content presentation (average 3.77). However, the design aspect (average 3.65) and technical aspects (average 3.35) still require improvement. This activity concluded that Canva is an effective tool for website development training, but improvements in design and technical aspects are needed for more optimal results. This training significantly contributed to the development of digital competencies of prospective early childhood education teachers.